Low molecular weight heparin versus acenocoumarol in the secondary prophylaxis of deep vein thrombosis - Lopaciuk, S; Bielska-Falda, H; Noszczyk, W; Bielawiec, M; Witkiewicz, W; Filipecki, S; Michalak, J; Ciesielski, L; Mackiewicz, Z; Czestochowska, E; Zawilska, K; Cencora, A (Thrombosis and haemostasis, 1999)
The aim of this study was to determine the efficacy and safety of subcutaneous weight-adjusted dose low molecular weight heparin (LMWH) compared with oral anticoagulant (OA) in the prevention of recurrent venous thromboembolism. In a prospective multicenter trial, 202 patients with symptomatic proximal deep vein thrombosis (DVT) were included. As soon as the diagnosis of DVT was confirmed by phlebography, 101 were randomly assigned to receive LMWH (nadroparin) for secondary prophylaxis and 101 to receive OA (acenocoumarol). Patients in both groups were initially treated with nadroparin in a dose of 85 anti-Xa IU/kg s.c. every 12 h. Secondary prophylaxis with either nadroparin, 85 anti-Xa IU/kg s. c. once daily, or acenocoumarol was continued for at least 3 months. Three patients in the LMWH group and 6 in the OA group were excluded from analysis for various reasons. During the one-year combined secondary prophylaxis and surveillance period, 7 of of the 98 evaluable patients (7.1%) in the LMWH group and 9 of the 95 evaluable patients (9.5%) in the OA group had a documented recurrence of venous thromboembolism (Fisher's exact test, p = 0.61). Of these, 2 patients who received LMWH and 7 patients on acenocoumarol had recurrences in the 3-month period of secondary prophylaxis. Four patients (4.1%) in the LMWH group developed bleeding complications during this study period, as compared with 7 (7.4%) in the OA group (Fisher's exact test, p = 0.37). There were two major bleedings, one in the LMWH group and one in the OA group. Eleven patients died, 5 (5.1%) in the LMWH group and 6 (6.3%) in the OA group. It is concluded that nadroparin in a dose of 85 anti-Xa IU/kg s.c. once daily provides an effective and safe alternative to oral anticoagulants in the secondary prophylaxis of DVT.